2017
DOI: 10.1016/j.jhazmat.2016.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Role of microgel formation in scavenging of chromophoric dissolved organic matter and heavy metals in a river-sea system

Abstract: We use riverine and marine dissolved organic carbon (DOC) polymers to examine their aggregation behavior, and to evaluate the roles of microgel formation in scavenging of chromophoric dissolved organic matter (CDOM) and heavy metals in a river-sea system. Our results indicate that riverine and marine microgels did not exhibit very much difference in size and self-assembly curve; however, the assembly effectiveness ([microgel]/DOC) of marine samples was much higher than riverine. Instead of concentration of DOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…It was clearly demonstrated that riverine and marine DOM polymers have the capacity for scavenging selected heavy metals via aggregation processes [ 75 ]. The presence of many anionic functional groups on the surface of polymers may provide cation exchange sites for complexing heavy or trace metals [ 76 ].…”
Section: Specific and Nonspecific Interactions Of Marine Gels With Metal Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was clearly demonstrated that riverine and marine DOM polymers have the capacity for scavenging selected heavy metals via aggregation processes [ 75 ]. The presence of many anionic functional groups on the surface of polymers may provide cation exchange sites for complexing heavy or trace metals [ 76 ].…”
Section: Specific and Nonspecific Interactions Of Marine Gels With Metal Ionsmentioning
confidence: 99%
“…For example, a higher level of colloidal Cu than colloidal Ni was found in coastal areas such as the Danshuei River estuary, Taiwan [ 77 ]; the San Francisco Bay estuary, USA [ 78 ]; and Narragansett Bay, Rhode Island [ 79 ]. This may indicate that gels binding with metals are generally affected by ligand interaction and types of polymers [ 75 ].…”
Section: Specific and Nonspecific Interactions Of Marine Gels With Metal Ionsmentioning
confidence: 99%
“…50 DOM that continuously aggregates and flocculates leads to the formation of larger flocs, which affects the binding ability of PFAAs. 28 Therefore, DOM with smaller size may have stronger binding ability to short chain PFAAs (Figure S1a−d), making the binding ability of soil solution and S-EPS to short chain PFAAs stronger than LB-EPS and TB-EPS. S-EPS content of cations (Ca, Al, K and Mg) on the surface of DOM in S-EPS was much higher than that in other medium (Figure S1e).…”
Section: Mechanisms Underlying Pfaas' Accumulation In Soil Solution A...mentioning
confidence: 99%
“…DOM is an important nutrition source for organisms , and is the most mobile component of soil organic matter. , DOM has a variety of negatively charged functional groups (e.g., carboxyl), aromatic side chains of proteins, and hydrophobic regions and polar subunits of humic acids, all of which make DOM negatively charged and amphiphilic . DOM is an important factor affecting the fate of pollutants, , such as PFAAs. However, research for DOM regulation on the multiphase distribution of PFAAs is mainly concentrated in the aquatic environment. …”
Section: Introductionmentioning
confidence: 99%
“…This is a significant process in the marine carbon and nutrient cycle, as well as in the formation of cloud condensation nuclei (Verdugo and Santschi, 2010;Verdugo, 2012). These intermingled networks, with nutrients/pollutants carried from the surface, are also accessible to microbes, making the microgel important in biological pumps, bioavailability of pollutants, the food web, and microbe sustenance (Kepkay, 1994;Carlson et al, 2002;Verdugo et al, 2004;Koron et al, 2013;Yamada et al, 2016;Shiu and Lee, 2017). Many recent studies have focused on the mechanism of DOC polymer aggregation and the parameters controlling microgel formation.…”
Section: Introductionmentioning
confidence: 99%